The legacy continues: ancillary relief on divorce in Ireland. Issue 3 (3rd July 2019) - O'Sullivan, Kathryn
ABSTRACT: On the 20th anniversary of the introduction of the Family Law (Divorce) Act 1996 in Ireland, this paper provides a descriptive account of the ancillary relief scheme applied in the jurisdiction on divorce and its critics. Part I presents a brief overview of the context in which divorce was introduced in Ireland – notably the pre-existing ban on divorce formerly found in Article 41.3.2° of the Irish Constitution – before outlining key aspects of the resulting 1996 legislation governing the provision of ancillary relief. Part II then describes the difficulties which have arisen in the application of this legislation, underlining, in particular, the unacceptable level of inconsistency apparent in judicial decision-making and the lack of over-riding principles. Part III finally places the spotlight on the lack of foreseeability for couples seeking to reach an out-of-court settlement and highlights the need for reform.